Epigenome-wide association study for sudden unexpected infant death. Issue 1 (December 2019) - Hashiyada, Masaki; Obayashi, Masahiro; Matsumoto, Tomohiro; Yoshimura, Sumitaka; Akane, Atsushi
Abstract: Many genomic variants associated with sudden unexpected death (SUD) have been found with the use of the next generation sequencing (NGS), and registered in the clinical pathogenetic variant databases such as SIFT, Poly-Phen2 and Grantham. In this study, we search additional variants by NGS analysis of genomic DNA extracted from the cadavers in the sudden unexpected infant death (SID) cases. Genomic DNA was extracted from the ventricular septum of three infants of SID cases, three infants died of myocarditis, asphyxia and Down syndrome, a 15 year-old boy died of SUD, and an adult died of intracerebral bleeding. After bisulfite treatment of DNA samples, methylation levels were measured using the Infinium MethylationEPIC BeadChip Kit and iSCAN system (Illumina). This system can check over 860, 000 methylation sites per sample. Methylation levels were compared among SID and other cases by GenomeStudio software (Illumina), and top 50 sites with increasing or decreasing methylation levels were obtained. When SID cases and a SUD case were compared, SID cases showed severe decrease in methylation level at cg16032134 site. This site exists in ATP10A gene coding ATPase class V type 10A enzyme and is related to several diseases such as asthma and chronic obstructive pulmonary disease (COPD).